Blends of poly(ester urethane)s and polyesters as a general design approach for triple‐shape memory polymers. Issue 9 (17th September 2020) - Karasu, Feyza; Weder, Christoph
Abstract: Poly(ester urethane)s represent a widely investigated class of thermoplastic polymers that exhibit a thermally triggered dual shape memory effect. This behavior is the result of urethane‐rich hard segments that define the permanent shape, while domains formed by the crystallizable polyester segments act as the memory switch. We show here that blending poly(ester urethane)s with a second polyester having a different melting temperature is a straightforward and possibly general approach to create triple‐shape memory polymers, in which two different temporary shapes can be programmed. To demonstrate this, we blended a poly(ester urethane) containing crystallizable poly(1, 4‐butylene adipate) segments with poly(butylene succinate) or poly(hexamethylene dodecanoate). The blends microphase separate and the different polyester segments form separate semicrystalline domains, which serve as switching elements that can be activated at different temperatures. The blends retain attractive mechanical properties and the shape memory characteristics are characterized by high fixities (70%–96%) and recovery rates (82%–94%). Abstract :